2016
DOI: 10.1097/tp.0000000000000973
|View full text |Cite
|
Sign up to set email alerts
|

A High Comorbidity Score Should Not be a Contraindication for Kidney Transplantation

Abstract: Despite the negative influence of comorbidity, patient survival after transplantation is remarkably good. This means that even patients with extensive comorbidity should be considered for transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 36 publications
(53 reference statements)
2
31
2
Order By: Relevance
“…In our cohort, the TUGT did not appear to provide any additional prognostic information for short‐term outcomes after consideration of recipient age and EPTS score, variables already well known to be associated with posttransplant outcomes . Although prior research on the TUGT has found the test to be associated with postoperative complications in several nontransplant surgical populations, the failure of the TUGT to provide prognostic information here may be explained by differences between the nature of the surgical procedures (orthopedic, colorectal, and cardiac surgical recovery may have different physical demands than kidney transplantation), as well as by the extended time interval between the test and the actual surgical procedure.…”
Section: Discussioncontrasting
confidence: 54%
“…In our cohort, the TUGT did not appear to provide any additional prognostic information for short‐term outcomes after consideration of recipient age and EPTS score, variables already well known to be associated with posttransplant outcomes . Although prior research on the TUGT has found the test to be associated with postoperative complications in several nontransplant surgical populations, the failure of the TUGT to provide prognostic information here may be explained by differences between the nature of the surgical procedures (orthopedic, colorectal, and cardiac surgical recovery may have different physical demands than kidney transplantation), as well as by the extended time interval between the test and the actual surgical procedure.…”
Section: Discussioncontrasting
confidence: 54%
“…However, in a study by Heldal et al[13], although increasing CCI scores predicted mortality in younger patients (ages 45-54 and 60-69 years), these were not predictive in those aged 70 years or older. Additionally, the applicability of the CCI, however, has been questioned in kidney transplant candidates[14]. In a recently published Dutch study, Laging et al[14] developed the Rotterdam Comorbidity in Kidney Transplantation (RoCKeT) score as an alternative to the CCI.…”
Section: Who Is An Appropriate Candidate?mentioning
confidence: 99%
“…Additionally, the applicability of the CCI, however, has been questioned in kidney transplant candidates[14]. In a recently published Dutch study, Laging et al[14] developed the Rotterdam Comorbidity in Kidney Transplantation (RoCKeT) score as an alternative to the CCI. The RoCKeT score is determined by the presence of cardiovascular disease (3 points), cerebrovascular accident (2 points), PVD (2 points), diabetes mellitus (2 points), liver disease (2 points), lung disease (2 points), malignancy (2 points) and human immunodeficiency virus (1 point).…”
Section: Who Is An Appropriate Candidate?mentioning
confidence: 99%
“…com or www.renalmed.co.uk/risk-calculator) driven from these risk scores are now available for this population [129]. Some of these indices are based on risk scores applied to the general population [109, 111, 118, 124], whereas others have also included pre- and post-transplant variables (Table 5). In general, they all accurately predict the risk of death or appearance of IHD and some attempts have been made to internally validate or compare the performance of these predictive models, mostly using registry data, but as yet, few have been externally validated in prospective studies.…”
Section: Prediction Of Mortality and Comorbidity In Waiting-list Patimentioning
confidence: 99%
“…By contrast, our Patient B would have a higher mortality risk (16% and 50%, respectively), as shown in Table 3. Lastly, as an alternative to the CCI, Laging et al developed the Rotterdam Comorbidity in Kidney Transplantation (RoCKeT) score using comorbidities similar to those in the CCI, including age [124]. Not surprisingly, comorbidity was highest (75%) in the oldest age group (70-79 years).…”
Section: Prediction Of Mortality and Comorbidity In Waiting-list Patimentioning
confidence: 99%